Numerical simulations of annular jet impingement behaviour - Teng, Justin Jia Ding (2017)
3-dimensional numerical simulations for an annular jet of Re = 2500 on a flat impingement plate at separation distances of 1Do, 2Do, and 4Do were conducted. Steady-state SST k-ω RANS and transient WALE LES turbulence models were used. The simulated flow profiles show good agreement with experimental observations, while further predicting regions of turbulence generation and mixing behaviour around the recirculation and impingement regions. The annular jet becomes asymmetrical and large-scale coherent structures dissipate beyond x/Do > 2, at which point transient numerical simulations facilitated the observation and analysis of smaller vortex structures otherwise undetectable by current experimental techniques. Spectral analysis of the jet axial velocity reveals three frequencies of oscillations with Sti = 0.068, 0.23, and 0.45.